Position statement of the Polish Society of Allergology and Polish Dermatological Society regarding the limited accessibility of materials necessary for patch testing. Part I: Technological and legal barriers - Roman Nowicki; Magdalena Czarnecka-Operacz; Elżbieta Grubska-Suchanek; Marta Kieć-Świerczyńska; Cezary Kowalewski; Beata Kręcisz; Jerzy Kruszewski; Maciej Kupczyk; Cezary Pałczyński; Jacek Szepietowski; Magdalena Trzeciak; Jolanta Walusiak-Skorupa; et al. (Alergologia Polska)
One of three Polish residents has contact allergy (Gell and Coombs type IV hypersensitivity reaction). The most frequent clinical manifestation of contact allergy is allergic contact dermatitis (ACD), affecting approximately one of 10 Poles ever in life, while 1 of a 100 has the symptoms at present. Cases of allergic reactions to implanted medical devices are also on the rise, causing failures of endoprostheses, implants, insulin pumps, pacemakers and vascular stents. At present, the only validated method and a gold standard of detecting type IV allergy are patch tests. The number of known haptens that can induce contact allergy amounts to 5200 and is still growing. Therefore, state-of-the art allergy and dermatology diagnosis requires patients’ access to a large number of diagnostic haptens. Contrary to the needs, legal regulations introduced in the EU hamper the accessibility to diagnostic haptens. This overregulation endangers citizens’ rights to state-of-the-art healthcare which may undermine the trust of citizens toward public institution in Poland and the EU. In the present position statement, experts of the Polish Society of Allergology and Polish Dermatological Society emphasize the gravity of the present situation and appeal for a partnership debate between competent authorities in the EU and Poland, allergy and dermatology medical societies, as well as patients’ organizations to find a best way of ensuring citizens’ access to necessary allergy diagnosis. First of all, the experts plea for urgent removal of bureaucratic barriers that limit the availability of diagnostic haptens that are indispensable in the state-of-the-art allergy and dermatology care.